Mediáció családjogi ügyekben: A gyökerekről és a sajátosságokról - Klisics, Diána (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2019)
Considering the development of both international and European law, the tendency for turning to Alternative Dispute Resolution methods has been noticeable for a long time and one of its types is mediation. The roots of mediation derive from ancient communities. Mediation is a special conflict handling method, its essence lays in the fact that a neutral third party (a mediator) mediates in the dispute of the two parties with the consent of both. Family mediation is the most frequently used form of mediation. Its undeniable significance is reflected in the time factor, the costs, the fulfilment of the concluded agreements and last but not least, the future relationship of the parties.